2000
DOI: 10.1002/1097-0339(200101)24:1<58::aid-dc1010>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Large-cell neuroendocrine carcinoma of the lung: Proposed criteria for cytologic diagnosis

Abstract: The category of large‐cell neuroendocrine carcinoma (LCNEC) of the lung, proposed to expand the traditional scheme of typical carcinoid, atypical carcinoid (AC), and small‐cell carcinoma (SCC), based on histologic features, has not been defined in cytology. We attempt to describe LCNEC cytologically. Cytologic features in 16 histologically confirmed LCNECs in fine‐needle aspiration biopsies, cell blocks, bronchial brushes, washes, and sputum specimens stained with Diff‐Quik, Papanicolaou, hematoxylin‐eosin, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 10 publications
3
36
3
Order By: Relevance
“…However, in cytological specimens, the cytoplasm was reported to be scant or stripped in the alcohol-fixed specimens [8], and the existence of both abundant cytoplasm and cytoplasmic stripping was reported in cytological specimens of LCNECs [7,9]. In our study, a large amount of clearly identified cytoplasm was frequently observed in all of LCNECs, and in one of seven SCLCs (14%).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, in cytological specimens, the cytoplasm was reported to be scant or stripped in the alcohol-fixed specimens [8], and the existence of both abundant cytoplasm and cytoplasmic stripping was reported in cytological specimens of LCNECs [7,9]. In our study, a large amount of clearly identified cytoplasm was frequently observed in all of LCNECs, and in one of seven SCLCs (14%).…”
Section: Discussionmentioning
confidence: 45%
“…Nuclear chromatin is fine and granular in bronchial brush cytology of LCNECs [7]. However, it is coarse and granular in fine-needle aspiration materials [7,8]. The difference in these results may be due to the different methods used to collect tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 87 patients, only five who had received cisplatin-based chemotherapy for recurrent tumor that was evaluable for the response. While LCNEC is difficult to diagnose prior to the start of treatment on the basis of the findings in biopsy or cytological specimens, the architectural neuroendocrine features may, more or less, be reflected in these small samples [19,20]. We, therefore, conducted a review of 567 autopsy cases of lung cancer, and identified 15 cases of LCNEC who had received cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, criteria have been proposed to diagnose LCNEC based on cytology. 47 The term 'large cell carcinoma, with neuroendocrine morphology' can be used for tumors resembling LCNEC by light microscopy but lacking proof of neuroendocrine differentiation by electron microscopy or immunohistochemistry. 10 The term 'combined LCNEC' is appropriate for those tumors containing components of other histological types of NSCLC, such as adenocarcinoma or squamous cell carcinoma.…”
Section: Differential Diagnosismentioning
confidence: 99%